Extension Agents’ Preference on Communication Media for Innovation Dissemination - Harsanto, Angela Nugraheni Putri; Untari, Dyah Woro; Widhiningsih, Diah Fitria (Jurnal Komunikasi, 2024)
Along with the development of extension, extension workers are expected to always be dynamic and follow existing changes. One of the changes made is the strategy of choosing media for extension in accordance with field conditions and the needs of farmers so that extension activities can achieve the planned targets. This study aims to determine the preferences of extension workers in choosing media for disseminating innovations and to determine the influence of the role of coworkers on the preferences of agricultural extension workers in using extension media in group communication in Sleman Regency, Yogyakarta. This study used a survey method and 40 extension workers in all UPTD BP4 Region I -VIII Sleman Regency were selected through simple random sampling. The analysis conducted to determine the preference of extension workers was the Cochran test. To determine the role of coworkers on farmers' preferences, a simple linear regression test was conducted. The results show that agricultural extension workers have a tendency to choose extension media that are generally used. In addition, the role of coworkers significantly influenced the preferences of agricultural extension workers.